2021
DOI: 10.1108/jabes-05-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

University lecturers' use of active teaching methods: a segmentation study concerning trust, empowerment, thinking styles and emotional intelligence

Abstract: PurposeThe purpose of this study is to examine the adoption of the active learning and teaching methods by university lecturers, taking into account the contribution of certain important factors, including trust, empowerment, thinking styles and emotional intelligence. In addition, this study further reveals the diverse nature of university lecturers with regards to their tendencies to adopt active teaching methods using the segmentation technique of marketing.Design/methodology/approachA structured survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
3
0
2
Order By: Relevance
“…Research has shown teachers' emotional wellbeing is pivotal to educational development (e.g. Nghiêm-Phú & Nguyễn, 2021). Hence, university teachers at AL-Baha University need to be given more encouragement through various incentives that would boost their emotional intelligence and thereby affect their choice of teaching methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown teachers' emotional wellbeing is pivotal to educational development (e.g. Nghiêm-Phú & Nguyễn, 2021). Hence, university teachers at AL-Baha University need to be given more encouragement through various incentives that would boost their emotional intelligence and thereby affect their choice of teaching methods.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the choice of teaching methods based on the earlier stated factors is meant to culminate in the production of learners who are creative, proactive, problem-solvers, good decision-makers, critical thinkers, and good communicators (Nghiêm-Phú & Nguyễn, 2021;Zenda, 2017). What is more, Shirani Bidabadi, Nasr Isfahani, Rouhollahi, and Khalili (2016) observe that a good teaching method help students question their preconceptions as well as motivates them to learn, by putting them in a situation in which they see themselves as authors of answers and as agents of responsibility for change?…”
Section: Research Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Metode mengajar dapat diartikan sebagai cara dosen dalam menyelenggarakan pembelajaran di dalam kelas (Netta, 2019;Nghiêm-Phú, 2022). Cara dosen membawakan materi di dalam kelas berpengaruh terhadap pemahaman mahasiswa, maka dari itu metode pembelajaran harus disesuaikan dengan bahan ajar.…”
Section: Pendahuluanunclassified
“…La combinación de habilidades comunicativas, inteligencia emocional, habilidades sociales y habilidades independientes proporciona un enfoque holístico esencial para abordar la complejidad de la enseñanza en la educación superior (Alavinia & Kurosh, 2012;Md-Ali et al, 2016;Castro-Paniagua, 2023). Los resultados también indican la importancia de la formación continua y el aprendizaje permanente (Tang, 2020), ya que los docentes necesitan adaptarse a entornos cambiantes y abrazar nuevas tecnologías (Rodríguez et al, 2021); se toma en consideración que la ética y el profesionalismo (Setiawan et al, 2020) son esenciales para mantener altos estándares de conducta, lo que contribuye a la construcción de la confianza y credibilidad en el entorno educativo (Nghiêm-Phú & Nguyễn, 2022).…”
Section: Cate-goría Habilidades Autoresunclassified